Basel IV implementation: A review of the case of the European Union - Mete Feridun; Alper Özün (Journal of Capital Markets Studies (JCMS), 2020)
Purpose Introducing radical changes to the methodologies for the determination of capital requirements, the final stage of the Basel III standards, which is referred to as "Basel IV" by the industry, will be a significant challenge for the global banking sector. This article reviews the main components of the new framework, analyses its ongoing implementation in the European Union and discusses its potential impact on banks, putting forward policy recommendations. Design/methodology/approach This article uses primary sources such as the publications by the Basel Committee for Banking Supervision and the European Commission. It also reviews the secondary sources, including both academic articles and analyses by various stakeholders. However, this article does not undertake any empirical analysis. Findings This article discusses that Basel IV will introduce strategic, operational and regulatory challenges for banks in scope. It also identifies a number of areas which are subject to further debate in the European Union such as the enhanced due diligence requirements under the new credit risk framework; governance, reporting and control rules under the operational risk framework; exemptions for certain derivative transactions under the credit valuation adjustment framework and the level of application of the capital floors within banking groups. This article concludes that the global implementation of the reforms by all jurisdictions and transposition into national banking laws concurrently with the European Union in line with the Basel Committee's implementation timeline is important from a financial stability standpoint. Originality/value The article presents an up-to-date and comprehensive review of the practical implications of Basel IV standards. It analyses the implementation of the standards in the case of the European Union, reviews the potential policy implications and presents recommendations for risk management practitioners.
Keywords: 330; Basel III; Basel IV; CRD 5; CRR 2; European Union